Passively Q-switched flashlamp pumped Nd:YAG laser using liquid graphene oxide as saturable absorber - N.N.Adnan; N.Bidin; N.A.M.Taib; H.Haris; M.Fakaruddin; A.M.Hashim; G.Krishnan; S.W.Harun (Elsevier, 2024)
Volume :80